2002
DOI: 10.1152/ajpendo.00014.2002
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose homeostasis in insulin-like growth factor-binding protein-3-transgenic mice

Abstract: Glucose homeostasis was examined in male transgenic (Tg) mice that overexpressed the human insulin-like growth factor (IGF)-binding protein (IGFBP)-3 cDNA, driven by either the cytomegalovirus (CMV) or the phosphoglycerate kinase (PGK) promoter. The Tg mice of both lineages demonstrated increased serum levels of human (h) IGFBP-3 and total IGF-I compared with wild-type (Wt) mice. Fasting blood glucose levels were significantly elevated in 8-wk-old CMV-binding protein (CMVBP)-3- and PGK binding protein (PGKBP)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 33 publications
7
69
0
3
Order By: Relevance
“…In obesity, AT Timp1 significantly increases (38,39), and mice injected with TIMP1 develop insulin resistance and systemic fatty acid overload (38). IGFBP3-treated adipocytes exhibit insulin resistance (36), and mice overexpressing Igfbp3 exhibit decreased glucose uptake in AT and muscle (37). Mice lacking Spp1 (osteopontin) are less likely to develop obesity and insulin resistance and exhibit less AT macrophage infiltration (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…In obesity, AT Timp1 significantly increases (38,39), and mice injected with TIMP1 develop insulin resistance and systemic fatty acid overload (38). IGFBP3-treated adipocytes exhibit insulin resistance (36), and mice overexpressing Igfbp3 exhibit decreased glucose uptake in AT and muscle (37). Mice lacking Spp1 (osteopontin) are less likely to develop obesity and insulin resistance and exhibit less AT macrophage infiltration (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that transgenic mice that over-express human IGFBP-3 cDNA exhibit fasting hyperglycemia, impaired glucose toleranc, and insulin resistance, without an apparent change in total IGF-I levels, and this was not clearly explained by disturbances in growth hormone secretion or adiposity (16).…”
Section: Discussionmentioning
confidence: 99%
“…Because IGFBP-3 is induced by hypoxia (16,26), it may be involved in angiogenesis (33) and glucose metabolism (48). These possibilities warrant further investigation in esophageal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%